Systematic treatment of charcot arthropathy of the midfoot - Cursino Fernandes, Milena Peloggia; Costa, Marco Túlio; Ferreira, Ricardo Cardenuto (Scientific Journal of the Foot & Ankle, 2018)
Objective: The objective of this study was to evaluate the efficacy of the systematic protocol developed in our institution for the treatment of Charcot arthropathy (CA) of the midfoot, specifically for cases anatomically classified as Brodsky type II. Methods: Sixty patients with type II CA were treated in the period between 1997 and 2017 following a systematic protocol adopted at our institution. Two patients (3%) were lost to follow-up, leaving a total of 58 patients with 64 feet (six had bilateral involvement). The mean follow-up time was 31 months (range 12 to 150), and the mean age was 55 years (range 27 to 73). Conservative treatment was indicated in 41/64 of the extremities (64%), and surgical treatment was indicated in 23/64 of the extremities (36%). We considered the result as satisfactory when the patient was able to walk independently, placing full body weight on the foot. The result was considered unsatisfactory when the affected extremity presented clear instability and was deformed to the point that it was not possible to fit it in a stabilizing orthosis or for the patient to place their weight on the foot during walking as well as when it was necessary to perform an amputation. Results: We obtained a satisfactory outcome in 54/60 patients (90%) and in 58/64 feet (91%). In 19/23 of the operated feet (83%) and 39/41 of the conservatively treated feet (95%), the result was atisfactory. Conclusion: The systematic treatment protocol developed at our institution allows achievement of a favorable prognosis regarding the clinicalfunctional outcome of type II CA, with conservative treatment being sufficient in most cases. Level of Evidence IV; Prognostic Study; Retrospective study.